The Rise and Fall of Church-Affiliated Universities in China: A Case Study of Qilu University's History - WANG Zheng, (Journal of Research for Christianity in China (JRCC), 2025)
Among the early missionary universities established on Chinese soil, Qilu University was the first founded by missionaries. Rooted in China, Qilu University embarked on various reforms beginning with its preparatory registration process. Qilu University's evolution closely mirrored and intertwined with the transformations of Chinese society, though it also faced numerous challenges. After its transformation, the university placed greater emphasis on teaching and research. Diversified funding sources bolstered its finances, significantly enhancing its academic standards. For Shandong Province, this not only advanced local education but also served as an exemplary model for Shandong University at the time. Over its eighty-eight years, the university cultivated numerous professionals who made outstanding contributions to the development of Shandong and the nation in fields such as medicine, education, and physics. In 1952, all missionary universities, including Qilu University, were dissolved. Faculty, students, buildings, and equipment were dispersed to other national universities, marking the complete integration of these institutions into China's educational system.
Keywords: Church University Qilu University Faculty Restructuring Sinicization